Implementation of a Regional Income and Expenditure Budgeting System Based on Minister of Home Affairs Regulations Number 21 of the Year 2011 in the Secretariat of the Indonesian Broadcasting Commission for East Java - Indra Setyawan Dwi Handoko (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine the implementation of the Regional Revenue and Expenditure Budget system based on Permendagri Number 21 of 2011 and standard cost analysis, as well as to determine the accountability reporting process based on PP no. 8 of 2006 and Government Accounting Standards. To get results based on these objectives, the author uses a problem-solving method. Data were obtained from interviews conducted by the author with the Regional Work Unit in the broadcasting sector. The results of the study indicate that in the preparation of a performance-based APBD, budgetary principles such as budget transparency and accountability, budget discipline, budget justice, budget effectiveness, and efficiency must be considered. The budget uses a performance model that prioritizes productivity achievement/results. The APBD is prepared based on performance, meaning that the government has made changes. These changes lead to an increase in the quality of social services and an increase in productivity. These two objectives encourage local governments to improve the institutional performance of the KPID Secretariat.